Competency Mapping of Front-line Staff: Key for Success inthe Organized Retail Sector - Rao, M. Mallika; Shankar, Dr. A. Udaya; Rao, Dr.M. Bhaskara (The journal of contemporary issues in business and government, 2022)
Competency is the ability of an individual to do a job effectively. Competency mapping is a process of mapping an individual’s competencies to job related skills. Competency mapping helps in identifying the gaps, if any, between job demands and individual competencies. Organizations can then intervene through effective training solutions for improving organizational performance. The study aims to identify the competencies required of employees in organized retail sector and identify gaps. Survey method was used to collect data through a structured questionnaire. The study is descriptive in nature. Hypotheses were tested. Radar Charts were constructed to identify the degree of competency gap of employee in each of the competencies. The study would be useful for practitioners and researchers for implementation in their contexts for organizational success.